The extent of the commitment of mathematics teachers by the quality of achievement tests from the perspective of educational supervisors in Madina - Alahmadi, Abdullah Musleh (Journal of Educational and Psychological Sciences, 2020)
The presented study is aimed at identifying the extent of commitment of mathematics teachers at the middle and high school levels using the quality of the achievement tests. This is performed by taking samples of the evaluation forms provided by mathematics supervisors in the education offices. It is geographically distributed in the teaching area of ​​Madinah for evaluating the questions of mathematics teachers for the academic year of 1438 /1439. 235 evaluation forms were randomly chosen from a total of 591 and all data was analyzed using SPSS program. The results of the middle school mathematics teachers showed a modest quality of the achievement tests after the analysis of the questionnaire achieving(2.03). The general framework of the test for middle school teachers was of interest to them because they obtained high arithmetic average (2.81). Moreover, high averages were obtained in specific aspects as per the following order: multiple choice questions, questions of right and wrong and essay question formats ranging from(1.18 -2.65). In contrast, other aspects showing poorer results included: pairing and filling format questions. However, the results of the high school mathematics teachers showed an average trend (2.16) in the quality of the achievement tests after analyzing the questionnaires. The general framework of the test for high school teachers was of interest to them because they also obtained a high arithmetic average (2.86). High averages obtained as per the following order: multiple choice questions, questions of right and wrong and essay question formats. Conversely, the other aspect of questions showed less significant results mainly in pairing and filling format questions (ranging 1.22-2.83).) Overall, the results indicated that there were no statistically significant differences between teachers of the two stages in the industry (significance value (α=0.05). This study included some recommendations that may improve the quality of the achievement testing specifically to mathematics teachers.